EFL teacher beliefs in boosting students’ critical thinking - Kummala, Alvina Zulfa; Anugerahwati, Mirjam; Astuti, Utari Praba (Universitas Muhammadiyah Sidoarjo, 2022)
The urgency of teaching critical thinking skills to the students currently cannot be neglected. The teacher holds essential role to prepare them to have great soft skills for their future lives. No matter what they want to be or what discipline of knowledge they want to emphasize, the ability to think critically will be beneficial for them. Hence, this paper aims to dig up teacher beliefs about the notion of critical thinking and how to teach it to the students. This research focused on EFL teachers of secondary level in Indonesia, particularly in Malang. By utilizing questionnaire and interview to collect the data, the results demonstrated that: (1) there are 85% of respondents believe in the importance of teaching critical thinking skills in secondary school area. (2) EFL teachers believed that it is very crucial for the teachers themselves to have the ability to think critically before teaching to their students, (3) they believed that by providing numerous activities such as debate, avoiding ‘lecturing’, problem solving and others could boost the students’ thinking skills. HIGHLIGHTS: Teachers have strong beliefs in the importance of critical thinking skills for the students Teachers should have the competence to think critically at first time Teachers should have the ability to provide various activities that can train the students to be critical thinkers.